(untitled) (Maharaja Surajmal Institute Law Journal, 2026)
India’s armed forces are currently undergoing an important phase of mod ernization and structural reform as the country adapts to evolving secu rity challenges. Since independence, India’s defence development has been shaped by early wars, regional tensions, and the strategic demands of the Cold War era. These experiences played a key role in shaping the structure, priorities, and strategic outlook of the Indian military. In recent years, several reforms have been introduced to address these issues. Important measures include the creation of the Chief of Defence Staff (CDS) and the Department of Military Affairs (DMA), along with policies promoting domestic defence production through initiatives such as “Make in India” and the SRIJAN programme. Greater attention has also been given to joint operations, advanced training, and the adoption of emerging technologies. India’s responses to border tensions with China and Pakistan, along with an increased focus on cyber capabilities and joint warfare preparedness, high light the shifting priorities of the country’s defence strategy. Rising defence expenditure and stronger support for indigenous defence industries further reflect efforts to enhance technological capability and strategic autonomy. Despite notable progress, institutional and procedural challenges remain. Continued policy support, improved coordination between services, tech nological investment, and attention to personnel welfare will be crucial for sustaining India’s long-term military modernization.